3-Hydroxybenzoate 6-Hydroxylase from Rhodococcus jostii RHA1 Contains a Phosphatidylinositol Cofactor - Montersino, Stefania; te Poele, Evelien; Orru, Roberto; Westphal, Adrie H.; Barendregt, Arjan; Heck, Albert J. R.; van der Geize, Robert; Dijkhuizen, Lubbert; Mattevi, Andrea; van Berkel, Willem J. H. (Frontiers in Microbiology, 2017)
3-Hydroxybenzoate 6-hydroxylase (3HB6H, EC 1.13.14.26) is a FAD-dependent monooxygenase involved in the catabolism of aromatic compounds in soil microorganisms. 3HB6H is unique among flavoprotein hydroxylases in that it harbors a phospholipid ligand. The purified protein obtained from expressing the gene encoding 3HB6H from Rhodococcus jostii RHA1 in the host Escherichia coli contains a mixture of phosphatidylglycerol and phosphatidylethanolamine, which are the major constituents of E. coli's cytoplasmic membrane. Here, we purified 3HB6H (RjHB6H) produced in the host R. jostii RHA#2 by employing a newly developed actinomycete expression system. Biochemical and biophysical analysis revealed that Rj3HB6H possesses similar catalytic and structural features as 3HB6H, but now contains phosphatidylinositol, which is a specific constituent of actinomycete membranes. Native mass spectrometry suggests that the lipid cofactor stabilizes monomer-monomer contact. Lipid analysis of 3HB6H from Pseudomonas alcaligenes NCIMB 9867 (Pa3HB6H) produced in E. coli supports the conclusion that 3HB6H enzymes have an intrinsic ability to bind phospholipids with different specificity, reflecting the membrane composition of their bacterial host.